The politics of fear and the securitization of African elections. Issue 5 (3rd July 2020) - Jenkins, Sarah
ABSTRACT: Elections are an important source of regime legitimation across sub-Saharan Africa, but they are increasingly being held amidst climates of fear, tension, and threat of ensuing violence. This article explores these climates of fear, arguing that they are, in part, a political construction; the result of strategic efforts to frame elections as a threat to peace and security, in order to legitimize tactics that tilt the playing field and intimidate political opposition. The article draws upon three diverse cases – the 2015 elections in Tanzania, and the 2016 polls in Zambia and Uganda – to explore the use of securitization discourses as a strategy of electoral manipulation. It argues that in these cases, the language of security was used to justify the construction of a "militarized" environment, and restrictions upon the freedoms of assembly and expression. Whilst these served to create a highly uneven electoral playing field, they were nevertheless tolerated by key stakeholders in the process.